Analisis Studi Kelayakan Bisnis pada Usaha Mainan Anak Ditinjau dari Aspek Keuangan - Ariesti Sopia; Aydiny Ummy Nurhali Harahap; Hadi Mubarak; Suhairi Suhairi (LPPM IAI Nasional Laa Roiba Bogor, 2022)
The financial aspect of the feasibility study is crucial because it covers all company profits. Understanding the financial aspect itself means the aspect that is functioned in the overall financial evaluation of the company. Therefore, this aspect is very crucial and requires accuracy in testing its feasibility in business. There are 7 aspects that need to be known, namely: the need for investment costs, sources of funds obtained, project balances and profit and loss statements, financial ratios to assess the company's ability, estimated investment costs. The purpose of the financial aspect analysis is to determine the investment plan through calculating the expected costs and benefits by comparing expenses and income, such as the availability of funds, the initial capital portfolio, the ability to repay these funds at a predetermined time and assess whether the company will be able to grow. Keep going. Keywords: Business Feasibility Study, Financial Aspect